Epistemological Base of African Traditional Herbal Medicine Among Primary School Teachers in Uganda. - Kuteesa, Disan (East African Journal of Traditions, Culture and Religion, 2021)
There is a noticeable usage of African Traditional herbal medicine in the treatment of physical and metaphysical diseases. This is largely due to the perceived high costs of orthodox medicine and the feeling that traditional herbs are more dependable. This research established the epistemological underpinnings of African traditional herbal medicine among primary school teachers in the Central Region of Uganda. The researcher used interviews, document analysis and focus group discussions to collect data from different schools. A total of eighteen (18) teachers were sampled, teachers claimed that African traditional herbal medicine is based on testimonial seeming, perceptual seeming, and memorial seeming. The study, therefore, found that the epistemological theory which can appropriately explain the basis of African Traditional herbal medicine in schools is the Bucket Theory of mind as advocated for by Karl Popper. The study recommends Poppers’ falsification theory in the operations of primary school teachers as a measure to do away with falsity content in the usage of traditional herbal medicine in schools